ICT Standards for Initial Teacher Training: A Public Policy in the Chilean Context - Silva Quiroz, Juan Eusebio (Education Policy Analysis Archives, 2012)
Several institutions, worldwide, have established ICT standards and are updating them to guide ICT usage by teachers and teacher education programs. Though Chile has the Enlaces project, a regionally and internationally recognized initiative for ICT insertion, it did not count on an ICT Standards Proposal to guide teacher education programs. For this reason, the Center for Education and Technology CET-ENLACES of the Ministry of Education of Chile (MINEDUC) has developed, since 2005, a policy to integrate ICT into Teacher Education. This article introduces the work done to define those standards and the actions taken to make them known and used by universities involved in teacher education.